A method of chromatic aberration compensation in holographic projection display based on a single spatial light modulator. Issue 1 (17th June 2015) - Wang, Cui; Wang, Di; Wang, Qiong‐Hua
Abstract In this paper, we propose a method of chromatic aberration compensation in holographic projection display based on a single spatial light modulator (SLM). By combining the hologram of the object with that of the digital lens, three color holograms with different focal lengths can be generated. Then, the SLM is divided into three parts, input three color holograms with different focal lengths to the SLM, and each occupies one‐third area of the SLM. We verify our method, and the results show its feasibility.